2022
DOI: 10.1186/s12875-022-01861-1
|View full text |Cite|
|
Sign up to set email alerts
|

Challenges with international medical graduate selection: finding positive attributes predictive of success in family medicine residency

Abstract: Background Criteria to select residents most likely to succeed, other than proficiency of their medical knowledge, is a challenge facing preceptors. International Medical Graduates (IMGs) play an integral role in mitigating the high demand for family medicine physicians across Canada. Thus, selecting IMG candidates that have a high probability of succeeding in Canadian educational settings is important. The purpose of this study is to elucidate qualitative attributes that positively correspond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Finally, in the original paper [1], the study protocol is described as asking preceptors "reflective questions, which provoked them to draw on examples of exceptional and poor IMG performers they have taught and selected, " (Pg 2) yet there is no indication in Table 2 of the original paper [1] of what questions may have been used to provoke examples of poor IMG performers, and therefore no way of knowing whether interview questions may have provoked biased or negative responses from participants that may have contributed to the bias and negative tone observed in this paper. Also interesting in the study design is that the authors chose to limit the study's focus to "examples of exceptional and poor IMG performers" and did not choose to expand the study to encompass "exceptional and poor CMG performers. "…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in the original paper [1], the study protocol is described as asking preceptors "reflective questions, which provoked them to draw on examples of exceptional and poor IMG performers they have taught and selected, " (Pg 2) yet there is no indication in Table 2 of the original paper [1] of what questions may have been used to provoke examples of poor IMG performers, and therefore no way of knowing whether interview questions may have provoked biased or negative responses from participants that may have contributed to the bias and negative tone observed in this paper. Also interesting in the study design is that the authors chose to limit the study's focus to "examples of exceptional and poor IMG performers" and did not choose to expand the study to encompass "exceptional and poor CMG performers. "…”
mentioning
confidence: 99%
“…In their paper "Challenges with international medical graduate selection: finding positive attributes predictive of success in family medicine residency, " [1] the authors report on their research into qualitative attributes that positively correspond to success in residency with the objective of assisting in the selection of International Medical Graduate (IMG) residents most likely to achieve success in family medicine residency. The authors found that positive predictors of IMG residents' success were: presence of a positive attitude, proficient communication skills, high level of clinical knowledge, and trainability.…”
mentioning
confidence: 99%